Metabolomic and transcriptomic analyses provide insights into the red pigmentation in loquat (Eriobotrya japonica) peel - Zhang, Yaling; Chen, Xiuping; Su, Wenbing; Deng, Chaojun; Jiang, Jimou; Zheng, Shaoquan (Frontiers in Plant Science, 2025)
Loquat (Eriobotrya japonica Lindl.) is a subtropical evergreen tree native to China. Generally, the pigments accumulated in the fruits of cultivated loquats are carotenoids rather than anthocyanins. In this study, we showed that the peel of ‘Shanpaisanhao’ loquats can accumulate anthocyanins and turn red. We further investigated the mechanisms underlying anthocyanin accumulation in the red-pigmented peels of ‘Shanpaisanhao’ loquats. RNA-seq analysis demonstrated that anthocyanin accumulation in loquat peel is associated with the upregulation of anthocyanin biosynthetic and transport genes as well as the transcriptional factor EjMYB10. Transient overexpression and dual luciferase assays showed that EjMYB10 could induce weak anthocyanin accumulation in tobacco leaves when co-expressed with PsbHLH3, and activate the promoters of EjF3′H, EjANS and EjUFGT. These results provide information for further elucidating the molecular mechanism of anthocyanin accumulation in the peel of SP3H loquat and for breeding of new red-pigmented loquat cultivars.